Finansowe aspekty rezerw - wybrane zagadnienia - Białas, Małgorzata (Financial Aspects of Reserves - Chosen Problems, 2009)
The paper is on chosen aspects of companies' reserves. The relevant Polish Accounting Act regulations and the International Financial Reporting Standards (IFRS) regulations are compared. Additionally, a percentage of reserves in the total assets is calculated and compared, based on a real situation of a few companies listed in Poland and in the UK.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 47-53